Food Insecurity: A Growing Threat to Nigeria’s National Security - Umoize Stanley; Iyanda Kamoru Ahmed (Recent Trends in Social Studies, 2024)
In Nigeria, the topic of food security has played a significant role in the national security equation. The study argues that though the strategic conception and approach are important in the articulation of threats analysis, the non-strategic conceptions like food security or insecurity are also important. It also examines the1erformance of this sector and the extent to which it could be employed as a catalyst to the defence of national security. The chapter finally recommends ways through which the country could achieve food self-sufficiency in order to solve future security problems. The issue of food and national security has become an important discourse in the international system. Food, one of the basic needs of humans cannot be neglected as people cannot be productive on empty stomachs. For some years now, food situations have improved especially in the developed countries where technology in agricultural production has reached advanced stages. The number of hungry individuals decreased slightly from 688 million in 1992–1994 to 639 million in 2002–2004 as a result of this development. Though many developed countries have sufficient food to meet the calorie requirement of its people the developing countries are yet to achieve food sufficiency. In sub-Saharan Africa, for instance, the number of hungry people has risen to over 19% in the last decade. It is disheartening to imagine that in most of these areas, agriculture is the main stay of their economies, all persons have means or accessand they are still hungry. Thus, in many developing countries the question of hunger has become a security threat.
Keywords: Food insecurity; Hunger; famine; mass destruction of farmland; poverty